Applications of simplified 3D FE model in seismic analysis for friction-damped posttensioned steel frame structures. (October 2021) - Zhang, Ni; Lu, Pingping; Zhao, Zhongwei; Wu, Xiufeng
Abstract: The post-tensioned (PT), energy-dissipating connection for steel frames has drawn the attention of many researchers due to its role in ensuring a favorable seismic performance. The energy-dissipating capacity of these frames is often improved by various friction mechanisms, such as friction-damped PT (FDPT) steel connections. Numerous researchers have investigated the seismic behavior of FDPT by using either the numerical or experimental method. However, previous studies have mostly relied on elaborate, time-consuming FE models, and analyzing a 3D frame structure is nearly impossible. To overcome these limitations, this paper proposed and analyzed a mechanical model of 3D FDPT as well as a 3D FE model of FDPT frame structures. The seismic responses of traditional and FDPT frame structures were also analyzed and compared. The results provide a foundation for the future analysis and design of PT frame structures.